Identifying Factors that Affect Repurchase Intention for Perfume on E-Commerce - Febriadi Soros, Algani Akbar; Fajar , Januar; Santoso , Vincent Christiant; Tamara , Dewi (Syntax Literate, 2025)
E-commerce is the result of technological advances. Currently, almost all products are available in E-commerce, one of which is perfume. Perfume is a product that cannot be separated from a person's lifestyle. There is a lack of previous research identifying the factors that impact the repurchase intention of perfume on E-commerce.The focus of this study is to determine the factors that influence the intention to repurchase perfume through e-commerce platforms. This study includes several factors, such as customer experience, brand image, product quality, price, and customer satisfaction. Data were collected from 204 respondents from the Jabodetabek area using a purposive sampling method with the criteria that respondents had purchased perfume in e-commerce. PLS-SEM was conducted to test the relationships in the conceptual model. The results showed that customer experience, brand image, and price significantly influenced customer satisfaction. While product quality did not show a significant impact to customer satisfaction. Many customers see price as an indicator of quality which is the most important factor in choosing a perfume because the quality of a perfume can be measured by the indicator of aroma durability, but not all use this indicator as an indicator of quality. Customer satisfaction has been proven to have a strong positive influence on repurchase intentions.